Big Books: Enhancing Grade 4 Reading Skills Through Descriptive Texts: Pemanfaatan Buku Besar dalam Meningkatkan Kemampuan Membaca Siswa Kelas 4 melalui Teks Deskriptif di Sekolah Dasar - Erinda Ambarani; Dian Rahma Santoso (Academia Open, 2023)
This study discusses the use big book in learning descriptive text skills for 4th grade students at SDN GRABAGAN. The purpose of this study was to determine the effect of big book on the ability to reading descriptive text. The method used in this study is quantitative with a pre-experimental design that applies pre-test and post-test instrument. By using the paired sample T-test, it shows that there are differences in the results of the average scores of the pre-test and post-test, namely for average value of the pre-test, and, for the post-test. This shows that the use of big book has an influence in learning reading skills. Highlights: The study explores the utilization of big books to enhance reading skills in grade 4 students through descriptive texts. A pre-experimental design with pre-test and post-test instruments was used to assess the impact of big book usage. The results indicate a significant difference in the average scores between the pre-test and post-test, demonstrating the positive influence of big book on learning reading skills. Keywords: Big book, Descriptive text, Grade 4 students, Reading skills, Elementary schools.